Internationalisation and the lived experiences of Non-South African postgraduate students in accessing higher education in South Africa - Banda, T.; Zungu, B. (South African Journal of Higher Education, 2024)
The internationalisation of higher education has resulted in an increase in student mobility from countries of their origin to experience a different kind of education elsewhere. South Africa absorbs most international students within Africa. According to Chasi and Quinlan (2021, 209) the Council for Higher Education reported that 6.5 per cent of the total number of enrolments in universities in South Africa are international students, which is a significant proportion of the student body. The success of these students contributes to raising the profile of South African universities as far as rankings are concerned as well as generating revenue for the institutions. This article explores the lived experiences of postgraduate international students at a university in South Africa. The aim of the article is to identify the opportunities and constraints that students experience, coming from outside South Africa to pursue postgraduate studies. Using Sen’s capability approach, the article endeavoured to unveil conversion factors that international students encounter while studying for their postgraduate programmes. A qualitative approach was employed to generate data through interviews with students who had completed their postgraduate studies. The findings revealed the capability to study as a “doing” that mattered to the students with the intention of ultimately attaining their postgraduate qualifications. Experiences along the way included both enabling and constraining factors such as immigration, cultural adjustments, supervision and institutional factors. There is a compelling need to revisit the processes of admission and immigration regarding international students aimed at benefiting both students and institutions.